MENTAL HEALTH IN THE QUR’ANIC PERSPECTIVE: A PSYCHOLOGICAL ANALYSIS OF QS. AR-RA‘D [13]: 28 AND QS. AL-BAQARAH [2]: 286: Kesehatan Mental dalam Perspektif Al-Qur’an: Analisis Psikologis atas QS. ar-Ra‘d [13]: 28 dan QS. al-Baqarah [2]: 286 - Ridwan; Nahyulia Liza Utari (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2025)
This article examines the concept of mental health from a Qur’anic perspective through a psychological analysis of QS. ar-Ra‘d [13]: 28 and QS. al-Baqarah [2]: 286. The study is motivated by the growing prevalence of mental health issues in modern society, which calls for multidimensional approaches, including the integration of psychology and religious studies. Employing a qualitative–descriptive approach, this research uses thematic analysis and Qur’anic exegesis of relevant verses, which are then contextualized within contemporary psychological theories. The findings indicate that the concept of ?uma’n?nah al-qalb in QS. ar-Ra‘d [13]: 28 represents a state of stable emotional regulation achieved through the practice of dhikr as an emotion-focused coping mechanism, while QS. al-Baqarah [2]: 286 emphasizes the principle of proportional life burdens that functions as a cognitive foundation for self-efficacy, resilience, and psychological hope. These findings suggest that the Qur’an provides both normative and psychological frameworks that are relevant for understanding and strengthening human mental health. This article contributes to the development of interdisciplinary studies between Qur’anic exegesis and psychology and offers a contextual and applicable Qur’an-based conceptual model of mental health.